Status Hukum Kepemilikan Hak Atas Tanah yang Tanahnya Telah Hilang Akibat Gempa Bumi di Cianjur - Putri, Catherina Amanda; Tjempaka, Tjempaka (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Proof of ownership of a plot of land is proven by the existence of a certificate and physical control so that if these two things are destroyed, the legal relationship between the owner and the land ends. There are several causes for the end of a person's land rights, one of which is that the land object has been destroyed due to a natural disaster. Because the term "destroyed land" is used in Article 27 of the UUPA, which refers to the abolition of land rights, the state is unable to provide legal protection for destroyed land, which results in a legal void. A normative legal research approach with a statutory approach was used for the study. The result of this study is a discussion of the form of legal protection by the National Land Agency regarding the reownership of land rights whose land has been lost due to natural disasters. Land rights holders can submit a report to the land service emergency response posts to report complaints of lost or damaged certificates due to natural disasters, and then the Land Office will conduct field research as the basis for issuing a replacement certificate.